(untitled) (Journal of the College of Basic Education, 2022)
This study was designed to show the effects of different concentrations of alcoholic extract of M.communis L. on the activity of MAO , AchE ,GOT, and GPT in human sera .The results showed that all concentrations of extract cause inhibition to enzymes activity ,the percentage of inhibition increased with increasing the extract concentration. Kinetic parameters were studied and the results showed that alcoholic extract of m.communis l. acted as competitive inhibitor with MAO ,AchE ,GOT, and GPT .